Religion, centers, and peripheries: notes on West Africa and the Arabs (Philology, 2023)
This article is based on the introduction to the Religion and Culture Seminar of the Center for the Study of Religions, Sofia University St. Kliment Ohridski. The seminar’s 2022–2023 interdisciplinary theme was “Center and Periphery in Religion and Society.” The text outlines the notion of center and periphery with the aim of framing a possible overall re-conceptualization, demonstrating why this notion remains highly relevant to our understanding of the intersection of religion and society. The analysis builds on preliminary notes on West Africa as an Islamic periphery to the Arab world. It then provides examples from the Middle East and Eastern Europe. The article argues that although a phenomenon looks peripheral from certain perspectives, this does not necessarily mean it is insignificant. In some cases, it might be more appropriate to speak of multiple interacting centers and peripheries rather than of one single center and a loose periphery.
Keywords: center and periphery; religion and society; Islam; West Africa; Arabs